Surviving pandemic control measures: The experiences of female sex workers during COVID-19 in Nairobi, Kenya - Hellen Babu; Rhoda Wanjiru; Mamtuti Paneh; Emily Nyariki; James Pollock; Jennifer Liku; Alicja Beksinka; Mary Kung’u; Pooja Shah; Tara Beattie; Joshua Kimani; Janet Seeley (Global Public Health, 2024)
At the beginning of the COVID-19 pandemic, the Kenya Ministry of Health instituted movement cessation measures and limits on face-to-face meetings. We explore the ways in which female sex workers (FSWs) in Nairobi were affected by the COVID-19 control measures and the ways they coped with the hardships. Forty-seven women were randomly sampled from the Maisha Fiti study, a longitudinal study of 1003 FSWs accessing sexual reproductive health services in Nairobi for an in-depth qualitative interview 4–5 months into the pandemic. We sought to understand the effects of COVID-19 on their lives. Data were transcribed, translated, and coded inductively. The COVID-19 measures disenfranchised FSWs reducing access to healthcare, decreasing income and increasing sexual, physical, and financial abuse by clients and law enforcement. Due to the customer-facing nature of their work, sex workers were hit hard by the COVID-19 restrictions. FSWs experienced poor mental health and strained interpersonal relationships. To cope they skipped meals, reduced alcohol use and smoking, started small businesses to supplement sex work or relocated to their rural homes. Interventions that ensure continuity of access to health services, prevent exploitation, and ensure the social and economic protection of FSWs during times of economic strain are required.